Violence against women : a global perspective - Nag, Paramita (Ed.) (ICFAI, 2009)
Gone are the days of chivalry. For all the progress the world has achieved, it has become a more violent place. TALK about the fair sex not getting a fair deal is now common. Significant numbers of the world s population are routinely subjected to tortu